2023
DOI: 10.14254/2071-789x.2023/16-1/6
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable e-commerce and environmental impact on sustainability

Abstract: Sustainability is one of the most important socio-economic-environmental topics of the time. Consumers are increasingly demanding companies to have eco-friendly approaches that ensure sustainable e-commerce. There is a great challenge to e-commerce business, taking into account that e-commerce is connected with frequent shipping, high return rates, and non-recyclable packaging, which cause a negative impact on the environment. The studies show that e-commerce is rapidly growing and widely accepted. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…The positive relationship observed between sustainability and online seller behavior (β = 0.936, p = 0.004) underscores the influence of sustainable practices on shaping the behavior of online sellers, aligning with previous research emphasizing the impact of sustainability initiatives on business conduct in the e-commerce sector [36]. Additionally, the positive association between online seller behavior and environmental impact (β = 0.886, p = 0.005) highlights the role of online seller actions in influencing environmental outcomes, as evidenced by studies investigating the environmental implications of e-commerce activities and supply chain management practices [49].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The positive relationship observed between sustainability and online seller behavior (β = 0.936, p = 0.004) underscores the influence of sustainable practices on shaping the behavior of online sellers, aligning with previous research emphasizing the impact of sustainability initiatives on business conduct in the e-commerce sector [36]. Additionally, the positive association between online seller behavior and environmental impact (β = 0.886, p = 0.005) highlights the role of online seller actions in influencing environmental outcomes, as evidenced by studies investigating the environmental implications of e-commerce activities and supply chain management practices [49].…”
Section: Discussionsupporting
confidence: 86%
“…they showed that sustainable practices directly influence seller behavior and decisionmaking processes [36]. Similarly, Ghaffar et al (2023) explored the role of sustainability values in shaping online retailers' strategies.…”
Section: Oláh Et Al (2023) Investigated Adopting Sustainable Practice...mentioning
confidence: 99%
See 1 more Smart Citation
“…This trend is further explored in a study by Štofejová et al [32], which discusses the environmental impacts of online shopping habits. Additionally, the importance of responsible consumption and return policies in e-commerce is emphasized, aligning with the findings of Oláh et al [33] and Oláh et al [34]. The integration of advanced technologies such as data analytics and AI for inventory optimization and waste reduction is another key strategy for aligning e-commerce with sustainable practices.…”
Section: Literature Reviewsupporting
confidence: 56%